Decision Support System For Determining Prospective Students' Department At Vocational School 1 Buer Using Simple Additive Weighting - Yuliadi, Yuliadi; Romero, Reynaldo; Rodianto, Rodianto (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Choosing a major is essential for students, especially junior high school students, who must choose the appropriate field. Vocational High School (SMK) is a formal education unit that organizes vocational education at the secondary education level as a continuation of junior high school. At SMK Negeri 1 Buer, the central determination system is carried out with a ranking system where the ranking system is carried out based on the order in which prospective students register for the primary major so that it cannot be determined according to the interests and talents of the students. The purpose of this major is so that students can be directed to receive lessons based on their abilities and skills. SMK Negeri 1 Buer has eight majors: Building Modeling and Information Design, Motorcycle Engineering and Business, Visual Communication Design, Light Vehicle Engineering, Welding Engineering, Industrial Electronics Engineering, Animation, and Graphic Engineering. Therefore, this decision support system can make it easier for schools to determine majors according to students' interests and talents. This study uses the Extreme Programming method as a system development method and Simple Additive Weighting for calculating the Decision Support System, using PHP as a programming language with the Codeigniter framework and MySQL database. With this SPK, SMKN 1 Buer can distribute students according to their interests and make it easier for students to choose majors according to their interests